Evidence for benefits of argumentation in a Mayan indigenous population - Castelain, Thomas (2016)
Group discussion improves on individual reasoning performance for a wide variety of tasks. This improvement, however, could be largely specific to members of modern, schooled, affluent Western cultures. In two studies, we observed the same improvement in the members of a traditional population—indigenous Maya from Guatemala. Two features of reasoning can account for this improvement: the myside bias, which precludes individuals from improving their performance on their own, and the ability to soundly evaluate others' arguments, which allows individuals to benefit from group discussions. These two features were observed in the traditional population studied: solitary reasoning performance was marked by the myside bias; individuals were more likely to be convinced by arguments for the correct answer rather than for a wrong answer. Together with previous evidence, the present results strengthen the conclusion that these features are adaptive features of reasoning.